MALNUTRITION IN YOUNG PAKISTANI CHILDREN - Hirani, Shela Akbar Ali (Journal of Ayub Medical College Abbottabad, 2012)
Background: Pakistan is a developing country with the second highest infant and child mortality rate in South Asia. In this region, malnutrition underlies much of the high infant and under five child morbidity and mortality rates. Although struggle to tackle the issue of malnutrition among young Pakistani children has been going on since many decades, till yet a realistic solution for this growing problem has not been found. Objective: This paper aims at reviewing literature to analyse the biological, maternal, socio-cultural, environmental, and politico-economical determinants of malnutrition among young children in Pakistan so that need based interventions can be recommended to prevent and overcome this growing issue. Methods: A systematic search of national, regional, and international literature was undertaken from peer-reviewed databases for 1991-2011 including MEDLINE, CINAHL, and PubMed. The search was augmented by reviewing the literature from WHO and UNICEF websites, books, local newspapers, and reference lists of articles thought to be relevant. Conclusion: Determinants of malnutrition among Pakistani children are multiple and are prevalent at the level of individual, family, and community. An analysis of biological, maternal, socio-cultural, environmental, and politico-economical factors indicate that most of these factors are interrelated; therefore, to tackle this issue, there is a need to plan composite interventions at the level of malnourished children, their families, and the Pakistani community. Keywords: Malnutrition, young children, Pakistan, determinants